2016
DOI: 10.1111/1747-0080.12279
|View full text |Cite
|
Sign up to set email alerts
|

School canteens: A systematic review of the policy, perceptions and use from an Australian perspective

Abstract: Aim This review aimed to identify current research related to the use of school canteens in Australia, with a focus on their food and drink policy. In Australia, approximately 25% of 5–17‐year olds are considered overweight and obese. Up to 41% of energy intake for children aged between 4 and 18 years is found to come from discretionary foods. The structured nature of the school environment provides an ideal environment to address childhood obesity and encourage a culture of healthy eating. Methods A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 22 publications
6
45
0
Order By: Relevance
“…First, low participation rates limit the generalisation of findings. While participation was low in comparison to other studies, this study supports and adds to 10 years of research in this area by further highlighting limited behavioural change and the difficulties encountered by school canteens in fostering this change . Second, only those interested in or having an adverse view to healthy canteens may have participated in the study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…First, low participation rates limit the generalisation of findings. While participation was low in comparison to other studies, this study supports and adds to 10 years of research in this area by further highlighting limited behavioural change and the difficulties encountered by school canteens in fostering this change . Second, only those interested in or having an adverse view to healthy canteens may have participated in the study.…”
Section: Discussionmentioning
confidence: 57%
“…Over the last 12–15 years, school canteens in Australia have been under intense pressure from the government and the public to improve the nutritional value of foods sold. Yet the findings from this study, when compared to the Australian public school canteen literature, highlights that little has changed. Similar to this study, literature spanning 10 years has shown that ‘unhealthy’ foods are more commonly purchased from public school canteens; there is inconsistent buy‐in from public school parents; and the role of public school canteens is to provide healthy food, promote healthy eating and support the school healthy eating curriculum .…”
Section: Discussionmentioning
confidence: 60%
“…A further barrier and major concern for many schools are inconsistent messaging from supplying unhealthy food options at school canteens/food services, driven by profit rather than a focus on health. National healthy school canteen guidelines exist, yet compliance within Australian schools is low . Additional support for schools to improve the food environment over and above the provision of health eating guidelines is critical, especially where profit is a competing goal.…”
Section: Discussionmentioning
confidence: 99%
“…National healthy school canteen guidelines exist, 31 yet compliance within Australian schools is low. 32 Additional support for schools to improve the food environment over and above the provision of health eating guidelines is critical, especially where profit is a competing goal. For example, we found school leadership who were concerned with the problem of childhood obesity to be the driving force behind establishing healthy food choices at one school.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Lawlis, Knox and Jamieson on the policy, perceptions and use of school canteens in Australia emphasises the importance of the evidence base and the need for higher quality research to bring about informed decision making . Their search identified 2741 studies, yet only 12 met the inclusion criteria; they noted the paucity of qualitative work, which ultimately limited the potential reach of the review process.…”
Section: Systematic Review As An Essential Implementation Ingredientmentioning
confidence: 99%